Factors associated with virological rebound in HIV-infected patients receiving protease inhibitor monotherapy. (13th November 2016) - Stöhr, Wolfgang; Dunn, David T.; Arenas-Pinto, Alejandro; Orkin, Chloe; Clarke, Amanda; Williams, Ian; Johnson, Margaret; Beeching, Nicholas J.; Wilkins, Edmund; Sanders, Karen; Paton, Nicholas I.
Abstract : Objective: The Protease Inhibitor Monotherapy Versus Ongoing Triple Therapy (PIVOT) trial found that protease inhibitor monotherapy as a simplification strategy is well tolerated in terms of drug resistance but less effective than combination therapy in suppressing HIV viral load. We sought to identify factors associated with the risk of viral load rebound in this trial. Methods: PIVOT was a randomized controlled trial in HIV-positive adults with suppressed viral load for at least 24 weeks on combination therapy comparing a strategy of physician-selected ritonavir-boosted protease inhibitor monotherapy versus ongoing triple therapy. In participants receiving monotherapy, we analysed time to confirmed viral load rebound and its predictors using flexible parametric survival models. Results: Of 290 participants initiating protease inhibitor monotherapy (80% darunavir, 14% lopinavir, and 6% other), 93 developed viral load rebound on monotherapy. The risk of viral load rebound peaked at 9 months after starting monotherapy and then declined to approximately 5 per 100 person-years from 18 months onwards. Independent predictors of viral load rebound were duration of viral load suppression before starting monotherapy (hazard ratio 0.81 per additional year <50 copies/ml; P  < 0.001), CD4 + cell count (hazard ratio 0.73 per additional 100 cells/μl for CD4 + nadir; P  = 0.008); ethnicity (hazard ratio 1.87 for nonwhite versus white, P  = 0.025) but not the protease inhibitor agent used ( P  = 0.27). Patients whose viral load was analysed with the Roche TaqMan-2 assay had a 1.87-fold risk for viral load rebound compared with Abbott RealTime assay ( P  = 0.012). Conclusion: A number of factors can identify patients at low risk of rebound with protease inhibitor monotherapy, and this may help to better target those who may benefit from this management strategy.